ANALISIS PENGARUH KUALITAS PELAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN KONSUMEN PADA BALAI KESEHATAN PARU MASYARAKAT (BKPM) DI SEMARANG - Arhamni, Yolis; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2015)
Need of healthy become one of important need of people. BKPM (centre ofcommunity lung health) is a community center that serves cheap healthy service for people in Semarang. As a service organization, satisfaction become main purpose of the service provider.This research is purposed to examine the impact of service quality and consumer value to patient satisfaction.The research is taken place at BKPM Semarang. The sample is 100respondents.Instrumentof questionnaire is used to collect the data. Regression analysis is applied to test the hypotheses of the research.Result of the analysis shows that service quality affect positively to patient satisfaction. Patient that receives a better service will have higher satisfaction. Consumer value also affect positively to patient satisfaction.Patient that receives a more value from the service will have higher satisfaction.